Role of Human Resource Management in the IT Sector: Examining the Impact of Human Resources on IT Project Performance (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Today, information technology is both a foundation for country growth and a standardpractise for leading and successful enterprises. Success in this sector is contingent on the success ofmicro and macro information technology initiatives, and this success cannot be achieved until allfactors, particularly the most precious element, namely human resources, are taken into account.Because project rules regarding human resources are evolving, the duties of IT project managers willalso alter in this regard. In this study, elements impacting IT project performance, such as the need torethink roles and pay greater attention to individual In the recruitment process, personality factors areimportant., education's involvement in the advancement of information technology projects, and so onhave been considered while discussing some of the problems in the fields of IT and human resources.